If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -15 = 42 Reorder the terms: -15 + 3a = 42 Solving -15 + 3a = 42 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 3a = 42 + 15 Combine like terms: -15 + 15 = 0 0 + 3a = 42 + 15 3a = 42 + 15 Combine like terms: 42 + 15 = 57 3a = 57 Divide each side by '3'. a = 19 Simplifying a = 19
| -16m^2+25=0 | | f(6)=36+1.531 | | f(6)=36+.1531 | | 2n+6=17 | | y=sw-st^3 | | y=4-3*-5 | | y=-20+10 | | 14+-3p=-20 | | 9p^2=747 | | (x+2)(x-3)=(x+9)(x-4) | | 0=-16t+38.8+3 | | (x+10)= | | 69-3x=7x-19 | | y=-8+8 | | x^2-7=44 | | 4-5u+12+16u=6u-18 | | 5e^4x-6=13 | | 214-5x=40x+24 | | 5x+101=9x-7 | | 15a+15=75 | | 6x-2-8=0 | | 2t(t+2)=1 | | P=b+a | | 6x+2x+3=360 | | x^2-3=33 | | 3x+9=5(2x-7)+3x | | 201-5x=31x+17 | | k^2+10=35 | | 15p=35 | | -4x^2=-4 | | y-2=-1(x+2) | | x/(x^2-16)-4/(x^2+5x+4) |